(untitled) (Huellas, 2024)
The present research starts by considering state educational establishments and their school architectures as spaces where part of the territorial construction carried out by the States is enabled. At the same time, they are spaces around which a multiplicity of territorialities are being developed as they are located in cities or in clustered or dispersed rural areas, therefore interacting with different social groups. This article seeks to identify how the space of the state school collaborates in the production of territoriality in contexts of indigenous-peasant communities located in mountain areas representing a very difficult access in the province of Tucumán, Argentina. At the same time, it is interesting to visualize the nuances that are generated in the interaction between the territorialities of the indigenous-peasant communities and the school institutions in these particular contexts. The starting point for this study was the identification and analysis of 14 rural schools located in the Cumbres Calchaquíes and Sierras de Quilmes mountain ranges, areas inhabited mainly by indigenous-peasant communities. Among the main results, it is proposed that in these specific contexts, the state territoriality sought by educational establishments and school practices is challenged and modified by local practices.